2016
DOI: 10.14254/2071-789x.2016/9-2/2
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Level and Factors of Institutional Rationality in Montenegro, Serbia and Bosnia and Herzegovina

Abstract: ABSTRACT. This paper analyzes the perception of the respondents in Montenegro, Serbia and Bosnia and Herzegovina regarding the level of institutional rationality and the deficit of basic selected factors that have a predominant impact on it. It uses and explains the conditional notion of institutional rationality as a specific form of bounded economic rationality. It starts from the basic hypothesis that during the long-lasting transition process there were four groups of inhibitors to the introduction and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…We succeeded, after several attempts, to collect approximately 50 answered polls from each of these countries, while the number of responders from academia was considerably greater in comparison to those from the field of industry and logistics. Besides, it is worth mentioning that we had previously done some analyses on the low level of institutional rationality in these three transitional economies, and concluded that it has a huge impact on the progressive transformations in these countries, including digital divide overcoming [24].…”
Section: Pilot Study Of Tagging Goods In Supply Chains Challenges In mentioning
confidence: 99%
See 1 more Smart Citation
“…We succeeded, after several attempts, to collect approximately 50 answered polls from each of these countries, while the number of responders from academia was considerably greater in comparison to those from the field of industry and logistics. Besides, it is worth mentioning that we had previously done some analyses on the low level of institutional rationality in these three transitional economies, and concluded that it has a huge impact on the progressive transformations in these countries, including digital divide overcoming [24].…”
Section: Pilot Study Of Tagging Goods In Supply Chains Challenges In mentioning
confidence: 99%
“…The ranking is made in such a way that to each group of criteria (C1-C4), listed in Table 1, the experts assigned the respective rank 1, 2, 3, or 4, in accordance to their subjective estimation based on the knowledge in the field, experiences, and intuition. Rank 1 belongs to the most serious set of barriers in The aggregate rank of the four selected criteria (C1-C4) over the respondents' estimations is determined by means of normalized average weight coefficients per criteria [24,25,26]. The idea of evaluating these weight coefficients is associated with the sum of ranks of each criterion, with respect to the assessments of the respondents (Formula 1):…”
Section: Survey Analyses and Their Validitymentioning
confidence: 99%
“…The fourth factor is the deficit of real, effective, and pluralistic institutional changes (Draskovic, 2006;Draskovic, Bauk, and Delibasic, 2016). L. Csaba (1995, pp.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…M. Draskovic, S. Bauk and M. Delibasic (2016) argue that their establishment and operation is enabled by the existence of informal and privileged combination of two basic institutional monisms (the market and the state regulation). This combination of institutional monisms has been dictated by the so-called "new elites", leading to institutional deficit in general, and institutional pluralism in particular.…”
Section: Theoretical Approachmentioning
confidence: 99%